Implementasi Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Critical Thinking Siswa dalam Pengamalan Nilai Pancasila Kelas V MI Tahdzibiyah Gempolpading - Fira Nur Arminatuzzahroh; Khotimatus Sholikhah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
This study aims to describe the critical thinking skills of fifth-grade students of MI Tahdzibiyah Gempolpading in understanding and practicing Pancasila values through the application of the Problem Based Learning (PBL) learning model. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and critical thinking tests with 10 students who were divided into 5 small groups. The results of the study indicate that the application of the PBL learning model has a positive impact on improving students' critical thinking skills. Of the 10 students who were the subjects of the study, 6 students showed prominent achievements in recognizing moral issues, evaluating actions, formulating logical solutions, and linking behavior to the values contained in Pancasila. Students became more active in discussions, expressed opinions with rational reasons, and dared to make decisions independently. Through the study of real problems such as cheating, littering, arguing with teachers, graffiti on walls, and bullying behavior, students were able to understand the values of Pancasila more concretely. Despite obstacles such as differences in ability levels and limited implementation time, the PBL model has proven effective in encouraging students to become more critical, wise, and responsible individuals.